2016
DOI: 10.7205/milmed-d-15-00480
|View full text |Cite
|
Sign up to set email alerts
|

Military Medics' Insight Into Providing Women's Health Care in Deployed Settings

Abstract: Although the advancement of women in the military continues to make strides-it is clear the availability of quality women's health care that women feel comfortable accessing may be its defining limitation. Medics are an excellent conduit for reinforcing these healthy messages and providing first-line treatment to deployed military women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, variations were expected due to differences in the methods and contexts of data collection in each of these studies. Compared with the self‐reported data in this study, lower prevalence rates were found when medical encounter surveillance data was used in the U.S. military study, 8 which would be expected given that not all servicewomen will choose to seek or have had access to medical care in some contexts 6,9,10,14,20 . In addition, previous studies have also focused on prevalence in defined time periods, such as periods of deployment 21 .…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…However, variations were expected due to differences in the methods and contexts of data collection in each of these studies. Compared with the self‐reported data in this study, lower prevalence rates were found when medical encounter surveillance data was used in the U.S. military study, 8 which would be expected given that not all servicewomen will choose to seek or have had access to medical care in some contexts 6,9,10,14,20 . In addition, previous studies have also focused on prevalence in defined time periods, such as periods of deployment 21 .…”
Section: Discussionmentioning
confidence: 64%
“…Compared with the self-reported data in this study, lower prevalence rates were found when medical encounter surveillance data was used in the U.S. military study, 8 which would be expected given that not all servicewomen will choose to seek or have had access to medical care in some contexts. 6,9,10,14,20 In addition, previous studies have also focused on prevalence in defined time periods, such as periods of deployment. 21 Regardless, the available evidence consistently highlights that genitourinary infections are common in servicewomen, affecting at least one-third during active-duty service, thus warranting consideration of prevention and management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations